PENGARUH DUE PROFESSIONAL CARE TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI KOTA BANDUNG - Faturachman, Tb. Aman; Nugraha, Angga (Program Studi Akuntansi FPEB UPI, 2015)
The purpose of this study is to know how the influence of professional care due to audit quality. Case study at Public Accounting Firm in Bandung City. Hypothesis in this research is due professional care have positive effect to audit quality. The research method used in this research is associative method. The population in this study were junior auditor and senior auditor who worked at Public Accounting Firm in Bandung City. Sampling using convenience sampling. Data used primary data collected from questionnaire results. In analyzing the data, this study uses a statistical analysis called product moment correlation. From the test results obtained a positive influence of 0.569 and the coefficient of determination of 32.37%. These results indicate that due professional care has an effect on audit quality of 32.37%.